2010
DOI: 10.2217/rme.10.63
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3D Culture System with Similarities to the Human Heart for Studies of the Cardiac Stem Cell Niche

Abstract: The described 3D culture model could be a valuable tool when studying the influence of different compounds on proliferation and differentiation processes in cardiac stem or progenitor cells in cardiac regenerative research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Although differences in expression patterns between RA and LV were observed for specific genes related to development, cardiac stem or progenitor cell markers such as C-KIT or OCT4, previously reported to be expressed in cardiac biopsies from the same group of patients (12,23), were, in this study, not identified as differentially expressed between the studied locations. This suggests that these cells are present in both locations.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Although differences in expression patterns between RA and LV were observed for specific genes related to development, cardiac stem or progenitor cell markers such as C-KIT or OCT4, previously reported to be expressed in cardiac biopsies from the same group of patients (12,23), were, in this study, not identified as differentially expressed between the studied locations. This suggests that these cells are present in both locations.…”
Section: Discussioncontrasting
confidence: 80%
“…The following TaqMan Gene Expression Assays were used: ALOX15 Hs00609608_m1, C3 Hs01100879_m1, FOS Hs00170630_m1, HLA-DRA Hs00219575_m1, PLA2G2A Hs00179898_m1, PLA2G4A Hs00233352_m1, PTGS1 Hs00377726_m1, PTGS2 Hs00153133_m1, STAT6 Hs00598625_m1, TPM2 Hs00268540_m1. CREBBP Hs00231733_m1 was used as a reference gene (12). Samples were analyzed in duplicates using the instrument 7900HT.…”
Section: Validation By Quantitative Real-time Pcrmentioning
confidence: 99%
“…In cardiac progenitor populations, the data on the expression of OCT-4 are more inconsistent. We and others have previously reported expression of OCT-4 in these populations [2,21], while others have failed to detect this expression [37,41]. It could be hypothesized that OCT-4 expression may be of importance to keep certain cardiac progenitor populations, including SP cells, in an undifferentiated state.…”
Section: Discussionmentioning
confidence: 81%
“…The following human TaqMan Gene Expression Assays were used: ABCG2 Hs01053796_m1, MDR1 Hs00184500_m1, C-KIT Hs00174029_m1, OCT-4 Hs01895061_u1, CD31 Hs0016 9777_m1, FLK1 Hs00176676_m1, VWF Hs00169795_m1, NKX2.5 Hs00231763_m1, and TNNT2 Hs00165960_m1. CREBBP Hs00231733_m1 was used as a reference gene [21]. The samples were analyzed in duplicates using the 7900HT instrument.…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%
“…Cultures of cardiospheres where cells have migrated and self-organized into spheres [1416] have shown an increase in the expression of progenitor markers such as C-KIT , but the cardiomyogenic potential of cells from these kind of cultures has been questioned [17]. In our previous study [18], we described a novel 3D model of high density spheres (HDS) cultured with or without cardiomyocytes. Results from that study suggested that this 3D model could harbor and nourish CPC, in which marker expression increased with culture time.…”
Section: Introductionmentioning
confidence: 99%